Evaluation of human and non‐human primate antibody binding to pig cells lacking GGTA1/CMAH/β4GalNT2 genes. (1st March 2015) - Estrada, Jose L.; Martens, Greg; Li, Ping; Adams, Andrew; Newell, Kenneth A.; Ford, Mandy L.; Butler, James R.; Sidner, Richard; Tector, Matt; Tector, Joseph
Abstract Background Simultaneous inactivation of pig GGTA1 and CMAH genes eliminates carbohydrate xenoantigens recognized by human antibodies. The β4GalNT2 glycosyltransferase may also synthesize xenoantigens. To further characterize glycan‐based species incompatibilities, we examined human and non‐human primate antibody binding to cells derived from genetically modified pigs lacking these carbohydrate‐modifying genes. Methods The Cas9 endonuclease and gRNA were used to create pigs lacking GGTA1, GGTA1/CMAH, or GGTA1/CMAH/β4GalNT2 genes. Peripheral blood mononuclear cells were isolated from these animals and examined for binding to IgM and IgG from humans, rhesus macaques, and baboons. Results Cells from GGTA1/CMAH/β4GalNT2 deficient pigs exhibited reduced human IgM and IgG binding compared to cells lacking both GGTA1 and CMAH. Non‐human primate antibody reactivity with cells from the various pigs exhibited a slightly different pattern of reactivity than that seen in humans. Simultaneous inactivation of the GGTA1 and CMAH genes increased non‐human primate antibody binding compared to cells lacking either GGTA1 only or to those deficient in GGTA1/CMAH/β4GalNT2. Conclusions Inactivation of the β4GalNT2 gene reduces human and non‐human primate antibody binding resulting in diminished porcine xenoantigenicity. The increased humoral immunity of non‐human primates toward GGTA1‐/CMAH‐deficient cells compared to pigs lacking either GGTA1 or GGTA1/CMAH/β4GalNT2 highlights the complexities of carbohydrate xenoantigens and suggests potential limitations of the non‐human primate model for examining some genetic modifications. The progressive reduction of swine xenoantigens recognized by human immunoglobulin through inactivation of pig GGTA1/CMAH/β4GalNT2 genes demonstrates that the antibody barrier to xenotransplantation can be minimized by genetic engineering.